Association of Sporadic Moderate-Vigorous Physical Activity with Cardiovascular Disease Risk Factors - A Systematic Review - VP Putri (ACI (Acta Cardiologia Indonesiana), 2017)
Background: Physical activity is an important factor controlling chronic diseases such as .....